1997
DOI: 10.3109/00365529709007676
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Histologic Subtypes and Location of Gastric Cancer andHelicobacter pylori

Abstract: H. pylori seroprevalence was higher in gastric cancer patients than in controls. The prevalence of H. pylori infection in intestinal-type gastric cancer was clearly higher than in the diffuse type and in the control group. An association was found between H. pylori infection and tumors located distally (antrum/pylorus).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 36 publications
2
19
0
1
Order By: Relevance
“…The World Health Organization and International Agency for Research on Cancer consensus group stated in 1994 based on epidemiologic and histological evidence has classified H. pylori as a definite class I carcinogen (IARC 1994;Abeba et al, 2014). Prevalence of H. pylori infection in gastric cancer varies from 19% to 94% according to study from Spain (Martin-de Argila et al, 1997). In one meta-analysis, H. pylori seropositivity was 82.4% for patients with gastric cancer (Haung et al, 1998).…”
Section: Clinical Characteristics and Helicobacter Pylori Status Of Gmentioning
confidence: 99%
“…The World Health Organization and International Agency for Research on Cancer consensus group stated in 1994 based on epidemiologic and histological evidence has classified H. pylori as a definite class I carcinogen (IARC 1994;Abeba et al, 2014). Prevalence of H. pylori infection in gastric cancer varies from 19% to 94% according to study from Spain (Martin-de Argila et al, 1997). In one meta-analysis, H. pylori seropositivity was 82.4% for patients with gastric cancer (Haung et al, 1998).…”
Section: Clinical Characteristics and Helicobacter Pylori Status Of Gmentioning
confidence: 99%
“…Tradicionalmente, la localización más frecuente del cáncer gástrico es la región antropilórica (cáncer gástrico distal) (5,6) , el cual se relaciona con el tipo histológico intestinal. Sin embargo, en las últimas décadas se ha observado un incremento de la frecuencia de los tumores de cuerpo y fondo (cáncer gástrico proximal) y de la unión esófago-gástrica (7)(8)(9) , lo cual se sospecha está asociado al cambio en la prevalencia también del tipo histológico de cáncer gástrico hacia el tipo difuso (10,11) .…”
Section: Introductionunclassified
“…Tumors of the body of the stomach tend to be associated with H. pylori more often than cardia tumors. Evidence of H. pylori infection is less frequently seen with diffuse-type gastric cancer (14). Molecular profiling studies have shown that intestinal and diffuse-type gastric cancers exhibit different patterns of gene expression (15), suggesting that these subtypes of malignancy evolve from different causative origins.…”
Section: Helicobacter Pylori As a Causative Agent For Gastric Adenocamentioning
confidence: 99%